CONSUMER LEGAL PROTECTION EFFORTS THROUGH HALAL CERTIFICATION POLICY FOR SMALL MEDIUM INDUSTRY IN PONOROGO - Rohmah Maulidia (Jurisdictie: Jurnal Hukum dan Syariah, 2022)
This article aims to further explore the halal certification policy for small and mediumsized industries in Ponorogo Regency after the issuance of the Law Number 33 of 2014 on Halal Product Assurance. This paper is an empirical legal research with a sociology of law approach with primary data based on interviews. Primary data and secondary data were analyzed by qualitative descriptive method. This article finds that the policy for mandatory halal certification for Small and Medium Industries in Ponorogo is based on the Law on Halal Product Assurance and other technical regulations for halal certification. Structurally, the authority for certification of Small and Medium Industries is in the Agency for the Halal Product Assurance Agency, Ministry of Religion, Ponorogo Regency. Culturally, the Small and Medium Industry Institute in Ponorogo welcomes the ease of halal certification by the Ministry of Religion of the Regency’s Halal Product Assurance Organizing Agency. This article has contributed to increasing the awareness of Small and Medium Industry actors, as well as the proactive efforts of the Halal Product Assurance Organizing Agency and the Ponorogo Regency Government to Small and Medium Industries in the form of technical guidance, workshops and socialization of the halal certification program.Artikel ini bertujuan menggali lebih jauh kebijakan sertifikasi halal bagi industri kecil dan menengah di Kabupaten Ponorogo pasca lahirnya Undang-undang Jaminan Produk Halal Nomor 33 tahun 2014. Tulisan ini merupakan penelitian hukum empiris dengan pendekatan sosiologi hukum dengan data primer berasarkan hasil wawancara. Data primer dan data sekunder dianalisis dengan metode deskriptif kualitatif. Artikel ini menemukan hasil bahwa kebijakan kewajiban sertifikasi halal bagi Industri Kecil Menengah di Ponorogo didasarkan pada adanya Undang-Undang tentang Jaminan Produk Halal serta peraturan teknis sertifikasi halal lainnya. Secara struktur, kewenangan sertifikasi Industri Kecil Menengah berada di Lembaga Badan Penyelenggara Jaminan Produk Halal Kementerian Agama Kabupaten Ponorogo. Secara kultur, Lembaga Industri Kecil Menengah di Ponorogo menyambut baik kemudahan sertifikasi halal Badan Penyelenggara Jaminan Produk Halal Kementerian agama Kabupaten. Artikel ini memiliki kontribusi untuk meningkatkan kesadaran para pelaku Industri Kecil Menengah menjaga hak dan kepuasan konsumen, serta adanya upaya proaktif Badan Penyelenggara Jaminan Produk Halal dan Pemerintahan Kabupaten Ponorogo kepada Industri Kecil Menengah dalam bentuk bimbingan teknis, workshop dan sosialisasi program sertifikasi halal.